Pengembangan Asesmen Digital Berbasis Kecerdasan Jamak untuk Mengidentifikasi Preferensi Belajar Anak Usia Dini - Ratna Dewi Sartika; Nita Priyanti; Chandra Apriyansyah (BOCAH: Borneo Early Childhood Education and Humanity Journal, 2026)
This study aims to develop a multiple intelligences-based digital assessment to identify early childhood learning preferences in South Tangerang City. The development of this assessment was motivated by the importance of child-centered learning that aligns with children’s characteristics and learning potential. This study employed a Research and Development (R&D) method using the 4D model, namely define, design, develop, and disseminate, with both qualitative and quantitative approaches. The developed digital assessment product, namely MULIA (Multiple Intelligences Assessment), along with its instrument, was tested through expert validation, instrument validity testing, inter-rater reliability testing, and practicality testing. The study involved three expert validators, two teachers in the needs analysis stage, ten teachers in the application trial stage, and 60 children aged 5–6 years. The expert validation results showed a feasibility level of 86.67%–95.56%, with an average of 91.11%, and an inter-rater reliability score of 0.928. Thus, the digital assessment was considered feasible and reliable for identifying learning preferences based on multiple intelligences. Based on user perceptions, the assessment was considered practical because it was easy to use, provided fast and data-based results, and helped teachers design learning activities according to children’s learning preferences. Therefore, this digital assessment has the potential to support the implementation of early childhood assessment in a more systematic, practical, and relevant manner in accordance with the needs of early childhood education.